Hybrid Literacy and Its Implementation: Challenges and Opportunities - Rifai, Irfan; Susanto, Fajar (JET ADI BUANA, 2018)
This study aims to illustrate the challenges and opportunities of implementing hybrid literacy at Junior High School level in Surabaya. Drawing from amalgamation of interviews with ten teachers who are responsible and concerned with the literacy programme in their schools, classroom observations and documents analysis, the findings indicate that the potential implementation of hybrid literacy within the schools in Surabaya tend to be disrupted by several aspects, all of which are surrounding social and cultural aspect. Social aspect such as students’ social condition and school facilities are being the principal challenges in implementing hybrid literacy, whilst cultural aspect such as the school orientation to a particular type of literacy is also prominent to inhibit the implementation of hybrid literacy practices. This study, to some extent, is able to portray the dynamic challenges of hybrid literacy application in the school literacy programmes within the city as well as the potential sources which positively help facilitate the implementation of the future literacy programme, hybrid literacy. Although this study can be used as a reflection of the actor’s lens involved in the literacy programme in Surabaya, the data is limited to three schools. The future study, therefore, should anticipate involving more schools and participants (teachers and students) to get richer data findings in regard with the challenges and opportunities of the implementation of the programme. Keywords: Hybrid Literacy, implementation, challenges, opportunity